2018
DOI: 10.1177/2056305118785639
|View full text |Cite
|
Sign up to set email alerts
|

How People Weave Online Information Into Pseudoknowledge

Abstract: Misinformation has found a new natural habitat in the digital age. Thousands of forums, blogs, and alternative news sources amplify fake news and inaccurate information to such a degree that it impacts our collective intelligence. Researchers and policy makers are troubled by misinformation because it is presumed to energize or even carry false narratives that can motivate poor decision-making and dangerous behaviors. Yet, while a growing body of research has focused on how viral misinformation spreads, little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 34 publications
0
26
0
1
Order By: Relevance
“…Therefore, the U&G theory has been adopted by social media researchers to realise the gratifications an individual gain from the usage of social media platforms. For instance, Introne et al (2018) established information seeking, information erudition, entertainment, and relational communication as some of the gratifications people obtain from the usage of social media. Similarly, Dunne et al (2010) found that information probing, relationship conservation and peer approval were associated with the usage of SNS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the U&G theory has been adopted by social media researchers to realise the gratifications an individual gain from the usage of social media platforms. For instance, Introne et al (2018) established information seeking, information erudition, entertainment, and relational communication as some of the gratifications people obtain from the usage of social media. Similarly, Dunne et al (2010) found that information probing, relationship conservation and peer approval were associated with the usage of SNS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies have attempted to explore the gratifications associated with the new media. For instance, Introne et al [ 12 ] proposed that the perceived gratifications of online news sharing were entertainment, interpersonal communication, information-seeking and information learning. Park and Blenkinsopp [ 13 ] proposed four gratifications derived from social media use, including information-seeking, socializing, entertainment, and self-status-seeking.…”
Section: Research Model and Hypothesismentioning
confidence: 99%
“…Narrative is a powerful tool that can enhance engagement and understanding of both truths and falsehoods [10]. Online, and specifically in the context of misinformation (e.g., conspiracy narratives, pseudoscience), research has shown that the construction and dissemination of narratives requires the efforts of numerous participants with differing levels of engagement [11]. It is dynamic, incorporating numerous discursive elements (multiple sources, hashtags, hyperlinks, memes, etc.)…”
Section: Introductionmentioning
confidence: 99%